Penguatan Kesadaran Demokrasi Bagi Mahasiswa Melalui Talk Show Dan Diskusi Interaktif Tentang Pemilu - Subaidi (BAHRI: Jurnal Pengabdian Kepada Masyarakat, 2025)
This empowerment program aims to enhance students' awareness and participation in elections through an interactive approach involving talk shows and discussions. The program emphasizes the importance of elections in a democratic society and how students, as agents of change, can actively engage in the political process. Through talk shows with competent speakers such as academics, KPU officials, and democracy activists, as well as group discussions, students are given the opportunity to understand the election procedures, their rights and responsibilities as voters, and the challenges faced in the digital political world. The results show an increase in students' understanding of their political rights and an encouragement to participate in upcoming elections. This program is expected to be an initial step in building a healthier political culture among the youth and strengthening Indonesia's democracy in the future